"Східні поеми" П. Куліша на перехресті азіатського містицизму і європейського романтизму - Лановик, М.Б.; Лановик, З.Б. (Слово і Час, 2019)
У статті проаналізовано поеми П. Куліша “Маруся Богуславка”, “Байда, князь Вишневецький”,
“Магомет і Хадиза” з погляду їх орієнтального підґрунтя. Основними джерелами “Східних поем”
є релігійні містичні системи (іслам, суфізм), твори європейського романтизму (Дж. Байрона,
П. Б. Шеллі) та філософія Спінози. Найяскравіше це втілилося в кордоцентричній доктрині.
Найбільше концепція Серця репрезентована в образі Жінки (категорія вічної жіночності). Східний
ракурс увиразнюється на тематичному рівні (концепти Істини, Любові, Вічності).
Особливості поетики виявляються в містичному мисленні. Мова поем алегорична, загадкова,
таємнича, що провокує подвійний сенс чи багатозначність інтерпретації, спонукає до розкодування
авторської образності та притчевості. Орієнтальний ракурс відкриває нові шляхи для розуміння
Кулішевих поем, його філософської доктрини й особистої життєвої позиції. The paper considers the main Panteleimon Kulish’s epic poems “Marusia Bohuslavka”, “Baida,
Prince Vyshnevetskyi”, “Muhammad and Hadiza” with the focus on their oriental background. The
idea of the eastern orientation of P. Kulish originates from the works of V. Shchurat, V. Ivashkiv and
others. The main attention is drawn to the fact that Kulish was considerably acquainted with eastern
cultures and religious systems (especially those of Near East and Middle East which he had to know
as a translator of Bible) and often used eastern concepts in his philosophic and literary works.
The researcher traces the influence of different factors in Kulish’s ‘Eastern poems’ at the levels of
ideology and imagery. The analysis reveals that the main sources of the author’s creative ideas were
the eastern religious mystical systems (such as Islam, Sufism) as well as European Romantic works,
in particular those by Lord Byron and P. B. Shelley, that were created under the same influence of the
eastern philosophic doctrines and philosophy of Spinoza. This content was most vividly embodied in
Kulish’s ‘cordocentric’ doctrine contrasting with ‘ratiocentric’ European philosophies. The emphasis on
the concept of the heart and emotional sphere is most eloquent and obvious in the image of Woman
that is interpreted as the eastern category of eternal femininity. The eastern focus is also noticeable
at the thematic level (the concepts of Truth, Love, and Eternity).
The main poetical peculiarities of the analyzed works are found in the mystical thinking and belief
in the sacred power of the Word. Thus the language of the poems is very allegoric, enigmatic, and
mysterious; it rather veils the main meaning than reveals it. So it results in double meaning or multiplicity
of interpretations and demands reading the poems with a search for a certain code or cipher for
decoding the author’s imagery and parabolic content. That is why the poems leave the impression
of paradoxical thinking and remain difficult for understanding which relate them to the works by Lord
Byron and P. B. Shelley (“Revolt of Islam”).
Probably this combination of Asian mysticism and European philosophies was the main reason
why some critics accused Kulish of being ‘non-synthetic’ personality (S. Yefremov). But oriental focus
reveals the new way for understanding and interpreting the poems by Kulish, as well as his philosophic
doctrine and personal position in life.